2017
DOI: 10.1167/17.12.22
|View full text |Cite
|
Sign up to set email alerts
|

Children's use of visual summary statistics for material categorization

Abstract: Although adults' ability to recognize materials from complex natural images has been well characterized, we still know very little about the development of material perception. When do children exhibit adult-like abilities to categorize materials? What visual features do they use to do so as a function of age and material category? In the present study, we attempted to address both of these issues in two experiments that we administered to school-age children (5–10 years old) and adults. In both tasks, we aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…There are conflicting results regarding whether or not infants and children might be sensitive to statistical properties of images like these. School-age children's material categorization suffers when synthetic textures are used (Balas, 2017), suggesting that their visual system is tuned to the natural appearance of materials. However, children in the same age range fail to show the same sensitivity as adults to fractal images that vary in their conformity to natural image statistics (Ellemberg, Hansen, & Johnson, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting results regarding whether or not infants and children might be sensitive to statistical properties of images like these. School-age children's material categorization suffers when synthetic textures are used (Balas, 2017), suggesting that their visual system is tuned to the natural appearance of materials. However, children in the same age range fail to show the same sensitivity as adults to fractal images that vary in their conformity to natural image statistics (Ellemberg, Hansen, & Johnson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…School-age children's material categorization suffers when synthetic textures are used (Balas, 2017), suggesting that their visual system is tuned to the natural appearance of materials. School-age children's material categorization suffers when synthetic textures are used (Balas, 2017), suggesting that their visual system is tuned to the natural appearance of materials.…”
mentioning
confidence: 99%
“…Children do not exhibit adult-like texture discrimination abilities until at least 10 years of age (Ellemberg, Hansen, & Johnson, 2012) and also do not appear to segment textures accurately until late in middle childhood (Sirteneau & Rieth, 1992). In previous work, we have also shown that regarding material perception specifically, some aspects of material categorization are also not adult-like during middle childhood, although this varies by material property (Balas, 2017). A key question regarding this slow development of adult-like abilities is whether or not ongoing improvements in material perception reflect changes in how visual information is used to inform material judgments or more general improvement in the efficiency of processes that support material perception.…”
Section: Introductionmentioning
confidence: 84%
“…A key question regarding this slow development of adult-like abilities is whether or not ongoing improvements in material perception reflect changes in how visual information is used to inform material judgments or more general improvement in the efficiency of processes that support material perception. In our previous work, we found that forcing children and adults to use visual summary statistics (Balas, 2006;Balas, Nakano, & Rosenholtz, 2009) to assess material properties affected categorization, but not matching, performance differently as a function of age (Balas, 2017). We interpreted these results as evidence that children had more or less adult-like abilities to compare and match materials using the information available in "mongrels" made from natural material images but had not yet established robust mappings between those features and category labels.…”
Section: Introductionmentioning
confidence: 87%
“…Critically, though there are more recent models that make it possible to match synthetic textures to their parent images more closely with regard to these higher-order structural features, the absence of this matching using simpler models makes it possible to examine how adult visual processing is affected by the absence of these relationships from natural images. In general, removing these statistical regularities from natural images incurs a measurable cost in a range of tasks including invariant texture matching (Balas & Conlin, 2015a) and material categorization (Balas & Schmidt, 2017). Moreover, observers' ability to distinguish between putative "scene metamers" that are defined by matching parametric texture features like those described above (Freeman & Simoncelli, 2011;Wallis, Bethge & Wichmann, 2016) suggests that the adult visual system is sensitive to the absence of higher-order statistical regularities that are absent from synthetic images rendered via these models.…”
Section: Introductionmentioning
confidence: 99%